Personalized contraceptive counseling: helping women make the right choice - Rodriguez J; Abutouk M; Roque K; Sridhar A (Dove Medical Press, 2016)
Janelle Rodriguez, Mona Abutouk, Karen Roque, Aparna Sridhar Department of Obstetrics and Gynecology, David Geffen School of Medicine at University of California Los Angeles, Los Angeles, CA, USAAbstract: Unintended pregnancy is a significant problem with medical, social, and economic consequences. Half of unintended pregnancies are a result of no contraceptive use; while the other half results from contraceptive inconsistencies, or method failure. Women have an array of contraceptive options to choose from, each of which differs significantly in terms of usage, efficacy, side effects, risks, and noncontraceptive benefits. Determining the best tool for communication is a challenge. In addition, the choice of contraceptive method differs among women with medical problems. Not all contraceptive methods are suitable for women with certain medical problems. In this review, we discuss different methods of counseling and the tools available for sharing contraception information.Keywords: birth control, decision aid, contraceptive